Zoological Collections of Germany The Animal Kingdom in its Amazing Plenty at Museums and Universities (Natural History Collections,, 2018)
This book is devoted to the knowledge of up to 250 years of collecting, organizing and preserving animals by generations of scientists. Zoological Collections are a huge resource for modern animal research and should be available for national and international scientists and institutions, as well as prospective public and private customers. Moreover, these collections are an important part of the scientific enterprise, supporting scientific research, human health, public education, and the conservation of biodiversity. Much of what we are beginning to understand about our world, we owe to the collection, preservation, and ongoing study of natural specimens. Properly preserved collections of marine or terrestrial animals are libraries of Earth's history and vital to our ability to learn about our place in its future. The approach employed by the editor involves not only an introduction to the topic, but also an external view on German collections including an assessment of their value in the international and national context, and information on the international and national collection networks. Particular attention is given to new approaches of sorting, preserving and researching in Zoological Collections as well as their neglect and/or threat. In addition, the book provides information on all big Public Research Museums, on important Collections in regional Country and local District Museums, and also on University collections. This is a highly informative and carefully presented book, providing scientific insight for readers with an interest in biodiversity, taxonomy, or evolution, as well as natural history collections at large.